HEDGING DEVICES IN ENGLISH AND BEHDINI-KURDISH: A CONTRASTIVE STUDY - SADDIQ, MAHDI TAWFIQ; TOMA, SHIVAN SHLAYMON (Journal of Duhok University, 2023)
This study presents a contrastive study of hedging devices in English and Behdini-Kurdish (also known as Northern Kurmanji). The appropriate identification, interpretation, utilization and translation of hedging devices are problematic for EFL learners and translators. Hedges are expressions used in speech and writing to avoid being committed to the truth conditionality of the statement, to express hesitation, to be uncertain, less direct, and to be polite. The study aims to provide a descriptive study of hedging in the two languages to identify similarities and differences between their hedging systems. This aim is achieved by reviewing some of the main classifications of the English hedges as the foundation for devising a classificatory system for hedges in Kurdish. Therefore, the study explores how hedging is voiced in both English and Kurdish and finds out that the English hedging system is more complex than the Kurdish one. Furthermore, it concludes that hedging in Kurdish is mostly lexicalized in nature due to the absence of epistemic modal auxiliaries as one of the main subcategories of hedging devices. The research also identifies another subclass of hedging devices which has not been addressed before in the available literature on hedging in the two languages. This subcategory is the use of the plural forms of some numbers and date expressions which are used when the exact number or date is not known by the writer as (thousands, millions, etc.) and (in the 1990s, etc.).